2008
DOI: 10.1029/2008gl035564
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a young volcanic origin of the Gamburtsev Subglacial Mountains, Antarctica

Abstract: The Gamburtsev Subglacial Mountains of East Antarctica are among Earth's most enigmatic mountain ranges. They are situated in the middle of Antarctica, buried under hundreds of meters of ice, and reach an elevation of more than 3000 m. These characteristics have given rise to speculation about their origin and composition, in particular whether they are a hotspot or remnants of ancient orogenic events. We studied fluvio‐deltaic sands from ODP Site 1166 in Prydz Bay which were deposited prior to the onset of Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 30 publications
(48 reference statements)
2
32
0
Order By: Relevance
“…[9] Several studies have documented U-Pb zircon dates of grains from the limited ice-free bedrock exposures in East Antarctica, including samples from the Prydz Bay coast Williams et al, 2007Williams et al, , 2010, the margins of the Lambert Graben, the Prince Charles Mountains [Boger et al, 2001;Carson et al, 1996Carson et al, , 2000Liu et al, 2007;Mikhalsky et al, 2006], and the Grove Mountains. These ages and field observations are extrapolated to determine the geology that may be beneath the ice based on limited geophysical evidence [van de Flierdt et al, 2008] (Figure 2). These studies showed a wide range of crustal formation ages in East Antarctica ranging from $3.5 Ga-0.5 Ga, with dominant peaks at 0.4-0.6 Ga, 0.9-1.2 Ga, 1.6 Ga, 2.2 Ga, 2.6-2.7 Ga, 3.0-3.1 Ga, and 3.4-3.5 Ga.…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Several studies have documented U-Pb zircon dates of grains from the limited ice-free bedrock exposures in East Antarctica, including samples from the Prydz Bay coast Williams et al, 2007Williams et al, , 2010, the margins of the Lambert Graben, the Prince Charles Mountains [Boger et al, 2001;Carson et al, 1996Carson et al, , 2000Liu et al, 2007;Mikhalsky et al, 2006], and the Grove Mountains. These ages and field observations are extrapolated to determine the geology that may be beneath the ice based on limited geophysical evidence [van de Flierdt et al, 2008] (Figure 2). These studies showed a wide range of crustal formation ages in East Antarctica ranging from $3.5 Ga-0.5 Ga, with dominant peaks at 0.4-0.6 Ga, 0.9-1.2 Ga, 1.6 Ga, 2.2 Ga, 2.6-2.7 Ga, 3.0-3.1 Ga, and 3.4-3.5 Ga.…”
Section: Geologic Settingmentioning
confidence: 99%
“…The EAIS is the largest and longest-lived ice sheet on Earth and encompasses $90% of the ice in Antarctica [Bamber et al, 2000]. One nucleation point for the onset of glaciation in East Antarctica in the early Oligocene is thought to be the subglacial Gamburtsev Mountains in the interior of the continent, which reach elevations of up to 4 km above sea level, but are entirely covered by ice [Bo et al, 2009;Cox et al, 2010;Pollard, 2003a, 2003b;Ferraccioli et al, 2011;Siegert, 2008;Siegert et al, 2008;Taylor et al, 2004;van de Flierdt et al, 2008]. Rapid expansion of the EAIS at $34 Ma is explained in recent models as being largely a result of global cooling related to declining atmospheric CO 2 levels [DeConto and Pollard, 2003a], with the development of the Antarctic Circumpolar Current and consequent thermal isolation of Antarctica acting as a potential trigger [Kennett, 1977].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the origin and compositions of the Gamburtsev Mountains have given rise to a significant number of speculations. Some scientists believed that the Mountains originated from the midCarboniferous inversion of an intracratonic basin during the Paleozoic era, or were generated by continentecontinent collision between East and West Gondwana during the last PrecambrianeCambrian Pan-African event (van de Flierdt et al, 2008;Liu et al, 2006;Hansen et al, 2010). However, other scientists argued that the Mountains were created by volcanic eruptions produced by a mantle plume, that is, a rising column of hot rocks within the Earth's interior which generates large volumes of magma as it approaches shallower depths (Sleep, 2006;Tulaczyk et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Verifications of the origin and age of the Gamburtsev Mountains are also extremely important to better comprehend subglacial environments and Antarctic ice sheet dynamics. Hence, understanding the crustal and upper mantle structure of the Gamburtsev Mountains is a major target of activities during the ongoing international Polar Year, which includes highly resolved geophysical measurements and drilling through the ice (van de Flierdt et al, 2008). Drilling through the ice sheet and penetrating into the subglacial bedrock are one of the primary goals of modern polar region research.…”
Section: Introductionmentioning
confidence: 99%
“…The Gamburtsev Subglacial Mountains form a major mountain range in central Antarctica. Sm -Nd isotope studies show no signs of young volcanism in the region, rendering a hot-spot-related origin for the mountain belt unlikely, although several other tectonic processes of mountain building have been proposed (van de Flierdt et al 2008).…”
mentioning
confidence: 95%